Research progress on the mechanism of cholesterol-25-hydroxylase in intestinal immunity - Zhong, Guoqiang; He, Chengcheng; Wang, Shanping; Lin, Chuangzhen; Li, Mingsong (Frontiers in Immunology, 2023)
Inflammatory bowel disease (IBD), a general term encompassing Crohn’s disease (CD) and ulcerative colitis (UC), and other conditions, is a chronic and relapsing autoimmune disease that can occur in any part of the digestive tract. While the cause of IBD remains unclear, it is acknowledged that the disease has much to do with the dysregulation of intestinal immunity. In the intestinal immune regulatory system, Cholesterol-25-hydroxylase (CH25H) plays an important role in regulating the function of immune cells and lipid metabolism through catalyzing the oxidation of cholesterol into 25-hydroxycholesterol (25-HC). Specifically, CH25H focuses its mechanism of regulating the inflammatory response, signal transduction and cell migration on various types of immune cells by binding to relevant receptors, and the mechanism of regulating lipid metabolism and immune cell function via the transcription factor Sterol Regulator-Binding Protein. Based on this foundation, this article will review the function of CH25H in intestinal immunity, aiming to provide evidence for supporting the discovery of early diagnostic and treatment targets for IBD.